CASPIAN PIPELINE GEOPOLITICS Competition between Western and Northern Oil and Gas Transport Routes to Europe - TEMNIKOV, Roman (CENTRAL ASIA AND THE CAUCASUS, 2019)
Since ancient times, the Caspian region has been known for its energy resources, which attracted the attention of leading world players. The struggle for control over hydrocarbon resources intensified after the collapse of the U.S.S.R. The new independent states—Azerbaijan, Kazakhstan, and Turkmenistan—were rich in energy resources but economically weak, making them targets for Russia and Western countries, which used their oil and gas companies to seek control over the hydrocarbon reserves of these states and influence their oil and gas sectors.The second stage of competition was the struggle for control over oil and gas export routes from the Caspian region to world markets. Initially, the newly independent states had no other way to transport hydrocarbons except to the north—through Russian territory. These pipelines were inherited from the Soviet Union; there were simply no others available at the beginning of the 1990s. Having thus become heavily dependent on Moscow, the new Caspian states began to work on creating alternative routes, one of which was the western route—from Azerbaijan through Georgia to Turkey and then to Europe. From 1998 to 2018, two oil pipelines and one gas pipeline were built in the western direction, which were subsequently expanded and modernized to increase capacity. As a result, a feud broke out between the two main routes for delivering Caspian oil and gas to Europe and world markets: the northern and western routes. The northern route is being lobbied by Russia, while the western route is supported by the U.S., EU, and Turkey. Depending on geopolitical preferences and the degree of dependence on one or another world locus of power, supporters of the northern and western routes emerged among the new countries of the Caspian.Thus, Azerbaijan has clearly supported the western route, Kazakhstan the northern one, and Turkmenistan has yet to make a decision, preferring to export gas along the northern route and oil along the western one. This article compares the strengths and weaknesses of both routes and the influence of geopolitics on the choices made by Baku, Nur-Sultan, and Ashghabad for exporting their hydrocarbons to Europe.